1,3,4-oxadiazóis: estratégias para síntese e derivatização a partir do ácido 4-oxopentanóico - Malavolta, Juliana Limana (2014)
This study shows strategies to prepare 1,3,4-oxadiazoles and derivatives from 4-oxopentanoic acid is reported. The compounds 4-(2-(5-substituted-1,3,4-oxadiazol-2-yl)ethyl)-2-(methylthio/phenyl)-6-(trifluoromethyl)pyrimidine; 7aa (5-H, 2-SMe); 7ab (5-Me, 2-SMe); 7ac (5-Ph, 2-SMe); 7ba (5-H, 2-Ph); 7bb (5-Me, 2-Ph); 7bc (5-Ph, 2-Ph); and 2-methyl-5-(2-(5-substituted-1,3,4-oxadiazol-2-yl)ethyl)-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidine; 8a (5-H); 8b (5-Me); 8c (5-Ph); were obtained through of reaction between the hydrazides trifluormetilated previously synthesized with orthoesters which lead to obtaining of product in yields of 55-98%. The synthesis of oxadiazoles-2-tiosubstituted through of reaction of hydrazides with carbon disulfide conducted the formation of compounds 5-(2-(methylthio/phenyl-6-(trifluoromethyl)pyrimidin-4-yl)ethyl)-1,3,4-oxadiazole-2-thiol; 9a (2-SMe); 9b (2-Ph); and 5-(2-methyl-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-5-yl)ethyl)-1,3,4-oxadiazole-2-thiol; 10; with yields of 84-97%. This compounds series were reacted with alkylating and acylating agents and derivatized to compounds 1,3,4-oxadiazoles 2-S-alkylated/acylated 5-(2-(methylthio/phenyl)-6-(trifluoromethyl)pyrimidin-4-yl)ethyl)-1,3,4-oxadiazol-2-yl-thiosubstituted; 11aa (2-SMe, 2-S(CO)Me); 11ab (2-SMe, 2-S(CO)CCl3); 11ac (2-SMe, 2-SCH2(CO)Ph); 11ba (2-Ph, 2-S(CO)Me); 11bb (2-Ph, 2-S(CO)CCl3); 11bc (2-Ph, 2-SCH2(CO)Ph); and 5-(2-methyl-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-5-yl)ethyl)-1,3,4-oxadiazol-2-yl-thiosubstituted; 12 (2-S(CO)Me). Series of hydrazones N’-(substituted)-3-(2- (methylthio/phenyl)-6-(trifluoromethyl)pyrimidin-4-yl)propanehydrazide, 13aa (Ph, 2-SMe); 13ab (2-ClPh, 2-SMe); 13ac (4-(N(Me)2)Ph, 2-SMe); 13ad (4-NO2Ph, 2-SMe); 13ae (furano, 2-SMe); 13ba (Ph, 2-Ph); 13bb (2-ClPh, 2-Ph); 13bc (4-(N(Me)2)Ph, 2-Ph); 13be (furan, 2-Ph); and N’-(substituted)-3-(2-methyl-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-5-yl)propanehydrazide; 14a (Ph); 14b (2-ClPh); 14c (4-(N(Me)2)Ph); 14e (furan); were also synthesized to use as precursors for 2,3-dihydro-1,3,4-oxadiazoles synthesis. N-substituted by reaction with acetic anhydride which led to the formation of N-acetyl-3-(2-(methylthio/phenyl)-6-(trifluoromethyl)pyrimidin-4-yl)propanehydrazide; 15a (2-SMe); 15b (2-Ph) with yields of 51-66%. Finally was investigated the oxadative cyclization of N-acyl hydrazones with trichloroisocyanuric acid to obtain 1,3,4-oxadiazoles it allowed to obtain 2-methyl-5-(3-yl-propanoate ethyl)-7-(trifluoromethyl)pyrazolo[1,5-a]pyrimidine and 2-(methylthio/phenyl)-4-(3-propanoate ethyl-yl)-6-(trifluoromethyl)pyrimidine with yields of 64-79%. All the synthesized compounds are new and their structures were confirmed by 1H, 13C NMR data and two-dimensional NMR techniques as well as mass spectrometry data.